Insights into UK Teachers' Wellbeing and Workload during the COVID-19 Pandemic Lockdown: Testimonies from the Silent Voices and Lessons Learnt - Beng Huat See (MDPI AG, 2024)
This paper presents the findings of a national survey of over 3400 teachers across all phases of education in England, 10 weeks into school closure. In this paper we report on the teachers' experiences and their testimonies of the effects of the lockdown on their wellbeing as they navigate the situation, trying to cope with teaching and adjusting to the use of new technology to deliver lessons in the confines of their home. We present their voices as they related their experiences and emotions in real time as the event unfolded. Teachers reported an increased workload with a proportionately large amount of time spent on administrative duties and planning, but less on actual teaching. On average, these teachers spent 15 h a week marking during the lockdown. Under half of the respondents said they felt happy and cheerful often, while only 17% said they did not feel this way often. Almost all teachers said they felt that what they were doing was important and worthwhile. The most common emotions expressed by teachers were fear, isolation, neglect, anxiety, and confusion. The inconsistency and lack of clarity of government guidelines added to teachers' anxiety. The negative media portrayal of teachers did not help. The majority of teachers reported little previous experience in online teaching and only a quarter were confident in using edtech to deliver remote teaching. Only a third of teachers said they were adequately supported for online teaching. This has implications for future teacher development and initial teacher training. However, there were equally numerous positive experiences reported by teachers. Active support from parents and consistent school-home communication were seen as important in ensuring students' continued engagement with learning. These lessons are beneficial in supporting the long-term sick and school refusers post-lockdown.